2018
DOI: 10.3390/ijerph16010073
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Discharge to a Skilled Nursing Facility after Transcatheter Aortic Valve Replacement Surgery

Abstract: An assumption regarding transcatheter aortic valve replacement (TAVR), a minimally invasive procedure for treating aortic stenosis, is that patients remain at, or near baseline and soon return to their presurgical home to resume activities of daily living. However, this does not consistently occur. The purpose of this study was to identify preoperative factors that optimally predict discharge to a skilled nursing facility (SNF) after TAVR. Delineation of these conditions is an important step in developing a ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In a study evaluating the discharge destinations of over 17 million hospital admissions of Medicare beneficiaries, patients who were discharged home had a 5.6% higher readmission rate compared with patients discharged to a skilled nursing facility (SNF), and there were no mortality differences between the discharge destinations 15 . Other studies that examined discharge destination after vascular surgery, total knee arthroplasty, transcatheter aortic valve replacement, or emergent general surgery found that patients discharged to an SNF, as opposed to their home, experienced worse outcomes, including higher readmission rates, morbidity, or mortality 16‐19 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study evaluating the discharge destinations of over 17 million hospital admissions of Medicare beneficiaries, patients who were discharged home had a 5.6% higher readmission rate compared with patients discharged to a skilled nursing facility (SNF), and there were no mortality differences between the discharge destinations 15 . Other studies that examined discharge destination after vascular surgery, total knee arthroplasty, transcatheter aortic valve replacement, or emergent general surgery found that patients discharged to an SNF, as opposed to their home, experienced worse outcomes, including higher readmission rates, morbidity, or mortality 16‐19 …”
Section: Introductionmentioning
confidence: 99%
“… 15 Other studies that examined discharge destination after vascular surgery, total knee arthroplasty, transcatheter aortic valve replacement, or emergent general surgery found that patients discharged to an SNF, as opposed to their home, experienced worse outcomes, including higher readmission rates, morbidity, or mortality. 16 , 17 , 18 , 19 …”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of frailty could identify patients at risk of developing delirium, falls, or deconditioning during hospitalization. This evaluation is essential to select an adequate treatment and improve outcomes, such as length of stay, readmissions, functional deterioration and death in elderly patients with severe AS [5,6]. However, it is not always possible due to the different criteria, a lack of uniformity and the significant variability observed in previous studies regarding frailty assessment.…”
Section: Introductionmentioning
confidence: 99%